1998
DOI: 10.1016/s1078-5884(98)80238-4
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendon bearing orthosis — Application as adjunctive treatment in healing of lower-limb tissue loss

Abstract: Early results from this anecdotal series are encouraging and a prospective study to determine the application of the PTBO in patients with neuropathic and neuropathic/ischaemic tissue loss is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Better long term functional results are achieved with the early involvement of a multidisciplinary rehabilitation team. Early mobilisation of patients with partial foot amputations on weight bearing custom made orthoses has shown promising results [47].…”
Section: Amputationmentioning
confidence: 99%
“…Better long term functional results are achieved with the early involvement of a multidisciplinary rehabilitation team. Early mobilisation of patients with partial foot amputations on weight bearing custom made orthoses has shown promising results [47].…”
Section: Amputationmentioning
confidence: 99%
“…On-going care within a specialist foot clinic using custom made shoes and insoles appear to improve functional outcome. Multidisciplinary team approaches such as healing of the ulcerated neuropathic foot using patella bearing orthoses has been described [56]. It has been reported that the pain of NFCI can be so severe as to require tricyclic antidepressants, and this should be instituted at an early stage [55].…”
Section: More Severe Injuriesmentioning
confidence: 99%
“…Rachelle Pretz, PT, DPT 1 , Cora Brown, MD 2 , William B. Hughes, MD 3 and Eric L. Altschuler, MD, PhD 1,2 From the 1 The patient's goal from therapy was to walk independently and decrease the burden of care on his family. Because of his burns the patient had impairments to his body structures, including decreased skin integrity, peripheral nervous system damage, and decreased ankle stability, all of which affected his ability to ambulate.…”
Section: Maximizing Functional Mobility In An Electrical Burn Patientmentioning
confidence: 99%
“…The PTB orthosis has been studied in diabetic patients with tissue loss of the lower limbs (1). A review of the literature on burns reveals that PTB orthosis has been used to treat one paediatric patient with equinovarus deformities post-thermal injury (2).…”
Section: Introductionmentioning
confidence: 99%